Analisis Nyala Torch Oksidasi Pada Oxy-Acetylene Terhadap Sifat Fisik Dan Mekanik Sambungan Las Pelat Baja Karbon Rendah - Wisnujati, Andika; Kartika, Rivaldy M (Semesta Teknika, 2017)
Oxy-acetylene welding is widely used in small workshops for car body repair, automobile and motorcycle exhaust, and other improvements using a maximum temperature of 3000oC that can not be done through another process. The purpose of this study was to analyze the effect of torque oxy-acetylene flame on the physical-mechanical properties in welding connection low carbon steel plates . The method used by using a low carbon steel plate 2 (two) pairs in a butt weld dimmension ofÂ  300 mm x 75 mm x 1 mm. After welding with oxy-acetylene in torch oxidation flame, the specimens wereÂ  examined through physical observation including microstructure and mechanical properties. Micro hardness vickers was used to evaluate the hardness. Tensile properties was determine using the universal testing machine. In the microstructure testing, there is a pearlite and ferrite whose become different dimensions as it is affected by the heat and air pressure of the weld. Mechanical testing that is tensile test obtained yieldpoint of the specimen A 125,17 N/mm2 and specimen B 126,55 N/mm2. The result of tensile strength specimen A 166,35 N/mm2 and specimen B 169,76 N/mm2. While the vickers test obtained the highest hardness that is 152.5 VHN in the welding area, and the lowest hardness number is 124,9 VHN in the heat affected zone.